Effect of exogenous fibrolytic enzymes cocktail incorporation on in vitro degradation and fermentation characteristics of oats straw based total mixed ration - BEIGH, YASIR AFZAL; GANAI, ABDUL MAJEED; AHMAD, HAIDAR ALI; FAROOQ, JAVID; SHEIKH, GOWHER GULL; RESHI, PARVAIZ AHMAD; HAQ, ZULFAQARUL (The Indian Journal of Animal Sciences, 2023)
The study was conducted to evaluate the effects of increasing doses: 0 (control), 0.20, 0.40, 0.60, 0.80 and 1.00 % DM of an exogenous fibrolytic enzymes (EFE) cocktail preparation on in vitro gas production (GP), nutrient degradability and fermentation characteristics of oats straw based Total Mixed Ration (TMR) with 60:40 roughage to concentrate ratio using sheep rumen liquor. The chemical composition of all the feed ingredients used for preparation of the experimental TMR (containing 16.63% crude protein and 90.51% organic matter) were within the normal ranges. Increasing the incorporation level of enzyme cocktail linearly as well as quadratically increased net GP, metabolisable energy content, short chain fatty acid concentrations and microbial crude protein production up to 0.60% DM level (L3) with no additional improvement at further higher levels. There were significant improvements in degradability of dry matter, organic matter and neutral detergent fibre up to the enzyme dose of 0.60% DM (L3) with constant values thereafter. Fermentation characteristics response to varying incorporation doses of EFE cocktail also revealed improvements up to 0.60% DM level (L3) with no effect on non-protein nitrogen contents. It is recommended that EFE cocktail incorporation dose of 0.60% DM to be used for efficient utilisation of oats straw based complete feed; however, this requires further testing by in vivo studies.